Role of computed tomography findings, complete blood count parameters and systemic inflammatory markers for predicting the severity in interstitial lung diseases: Markers Predicting Prognosis in ILD - Sulku, İbrahim; Özer Gökaslan, Çiğdem (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background and Objectives: The present study aimed to find quantitative and semiquantitative methods to detect the development of fibroproliferative processes at an early stage and predict the severity and prognosis of the disease in interstitial lung diseases (ILDs) using High-Resolution Computed Tomography (HRCT), Pulmonary Function Tests (PFTs) and Complete Blood Count (CBC) parameters.Materials and methods: A total of 63 patients (26 female and 37 male) who were admitted to our hospital between January 2014 and January 2018, whose follow-ups were regular and who underwent HRCT, PFT, and CBC examinations on the same day, were included in our study. The median age of the patients included was 65 years (range: 47-79).Results: There were significant differences among the mild, moderate, and severe form ILD groups created using the Warrick scoring system for NLR, neutrophil count, and PNR values (p = 0.025, 0.035, 0.006, respectively). Also, there were significant differences among the groups for FVC, FEV1/FVC, PAD, RAA, RV/LV ratio, MLnMD, and MLnC values. Correlation analyses between the parameters revealed significant relationships between Warrick Score, and NLR and neutrophil count, PNR, FVC, FEV1/FVC, PAD, RAA, RV/LV ratio, MLnMD, and MLnC .Conclusions: The results of the present study suggested that NLR, neutrophil count, and PNR values could be used as objective evaluation criteria to determine the severity and prognosis in interstitial lung diseases. Also, usage of Warrick Score, FVC, FEV1/FVC, PAD, RAA, RV/LV ratio, MLnMD, and MLnC values could provide quantitative and semiquantitative data for an objective evaluation. Carrying out multicenter studies and creating a scoring system using these parameters could create standardization in determining the prognosis of patients with ILD.